NUMERICAL ANALYSIS ON HYDRAULIC PERFORMANCE OF THE FIXED FREE SURFACE H-TYPE BREAKWATER - SILAVARAJ, THINAGRAN (2020)
A breakwater is a maritime structure created to ensure harbours and shorelines are secure from the full effect of waves. In general, breakwaters can be characterized into three core types which are rubble-mound structures, floating breakwater and vertical wall structures. In this case, H-type floating breakwater was chosen as main literature for this project due to the breakwater configurations was proven to work efficiently as a wave energy attenuator apart from being a good antireflection structure and energy dissipater. Another author further modified the breakwater to a fixed free surface structure and it was explicitly tested and examined on his hydraulic performances. Based on the study, the hydraulic performances of the breakwater still deploy a strong agreement in dampening the wave.